A Key Agreement Protocol Based on Superior Fractal Sets - Shafali Agarwal; Ashish Negi (International Journal of Advances in Applied Sciences, 2014)
The fractal properties endeavour of inventing new techniques because of its complex structure. Mandelbrot and Julia sets are created by using the same function but in different parameter plane. This strong connection of fractals leads its use in the field of cryptography. In the proposed protocol, superior Mandelbrot set function is used to calculate the public keys with the help of chosen private keys as input parameter whereas superior Julia set function is used to generate a shared private key by using public keys of either side for both parties which is impossible to hack by an intruder.